Regional Income Analysis Of Tourism Sector In Kaur District - Eko Ariadi; Ahmad Soleh; Ida Ayu Made Er M.G (Penerbit Jurnal Indonesia, 2021)
This study aims to analyze the regional revenue of the tourism sector in Kaur Regency. This research problem is limited to the regional revenue analysis of the tourism sector in Kaur Regency based on the factors that affect the increase in the tourism industry according to Yoeti (2014: 89) which consists of the number of tourists and the number of hotel occupancy against PAD of the tourism sector in Kaur Regency in 2015 - 2019. Data collection was done using documentation and analysis methods with multiple linear regression analysis, test of determination and hypothesis testing. From the calculation of the multiple linear regression equation that Y = 170.508 + 3,340X1 + 9,447X2, because the direction of the regression shows a positive value, it means that the number of tourists and the number of hotel occupancy have a positive effect on Regional Original Income (PAD). The coefficient of determination is 0.829, which means that changes in the independent variables are able to explain the dependent variable at 82.9%, while the remaining 17.1% is explained by other factors outside the independent variables used in this study. Based on the test results with the t test, all independent variables have a small significant value of 0.05, it means that partially there is an effect on the number of tourists and the number of hotel occupancy on Locally-Generated Revenue (PAD) in Kaur Regency. Based on the results of hypothesis testing with the F test, the hypothesis is made that the number of tourists and the number of hotel occupancy affects the Regional Original Income (PAD) in Kaur Regency. The results of statistical calculations show a significance value of 0.05.